Comparison of the Hardness of Novel Experimental Vinyl Poly Siloxane (VPS) Impression Materials with Commercially Available Ones. (9th February 2022) - Ud Din, Shahab; Chaudhary, Farooq Ahmad; Ahmed, Bilal; Alam, Mohammad Khursheed; Parker, Sandra; Patel, Mangala; Javed, Muhammad Qasim
Abstract : Purpose . To determine the hardness and Young's moduli of both commercial and experimental vinyl poly siloxane (VPS). Methods . The purpose of this study was to develop a medium-bodied experimental (Exp-I, II, III, IV, and V) VPS impression materials and to analyse their effects on hardness and Young's modulus and compare them with three commercial VPS materials (Aquasil, Elite, and Extrude) using Shore A hardness tester. Measurements were recorded after 1, 24, 72, and 168 hours of mixing. The results were analysed with one-way ANOVA and post hoc Tukey's test using the SPSS PASW statistical 22 software. Results . Commercial and experimental vinyl polysiloxane exhibited higher Shore A hardness values with time (i.e., 1 hour after mixing, 24 hours after mixing, 72 hours after mixing, and 1 week after mixing). All Comml and Exp VPS demonstrated a significant increase (ANOVA, p < 0.05 ) in hardness at increasing time points. Generally, all commercial VPS exhibited significantly higher values for Shore A hardness compared to all Exp formulations. For commercial products, Elt M presented significantly highest values at all-time points followed by Aq M then Extr M. Exp-I was significantly harder than all other Exp VPS at all-time points. Young's modulus values were directly related to Shore A hardness; materials with higher Shore A hardness values had higher Young's moduli. Conclusion . Continued polymerisation of elastomeric impression materials results in increased hardness over time. Hardness, Young's moduli, and rigidity of the set commercial and experimental VPS materials were within the required limits. Shore A hardness and Young's moduli were directly proportional to each other, and commercial and experimental materials had enough rigidity to contain the stone during pouring.